Ultrasound-Triggered on Demand Lidocaine Release Relieves Postoperative Pain - Chen, Xiaohong; Zhang, Jianfeng; Yu, Yan; Wang, Haoran; Ma, Genshan; Wang, Di; Cao, Hanzhong; Yang, Jianping (Frontiers in Bioengineering and Biotechnology, 2022)
Safe and non-invasive on-demand relief is a crucial and effective treatment for postoperative pain because it considers variable timing and intensity of anesthetics. Ultrasound modulation is a promising technique for this treatment because it allows convenient timed and noninvasive controlled drug release. Here, we created an ultrasound-triggered lidocaine (Lido) release platform using an amino acid hydrogel functioning as three-dimensional (3D) scaffold material (Lido-PPIX@ER hydrogel). It allows control of the timing, intensity and duration of lidocaine (Lido) to relieve postoperative pain. The hydrogel releases Lido due to the elevated reactive oxygen species (ROS) levels generated by PPIX under ultrasound triggering. The Lido-PPIX@ER hydrogel under individualized ultrasound triggering released lidocaine and provided effective analgesia for more than 72 h. The withdrawal threshold was higher than that in the control group at all time points measured. The hydrogel showed repeatable and adjustable ultrasound-triggered nerve blocks in vivo, the duration of which depended on the extent and intensity of insonation. On histopathology, no systemic effect or tissue reaction was observed in the ultrasound-triggered Lido-PPIX@ER hydrogel-treated group. The Lido-PPIX@ER hydrogel with individualized (highly variable) ultrasound triggering is a convenient and effective method that offers timed and spatiotemporally controlled Lido release to manage postoperative pain. This article presents the delivery system for a new effective strategy to reduce pain, remotely control pain, and offer timed and spatiotemporally controlled release of Lido to manage postoperative pain.